(3GdOhGQ GdYfUQjI GdeSJNQLI ef GdRGjQLI GdSHJjIs
(3ChdgG (B:s
(3GdMeO ddg GdhGMO dGef YOO eMShH , GdefaQO HYde HhGWf GdZjhH s
(3BNQgG (B:s
(3JeJ HMeOg JYGdi hMSf Yhfg GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B51s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(58 (3c(B) s
Keywords: (3GdMQha h GdChaGbs